PEMIKIRAN IBNU MALIK TENTANG OTORISASI HADITS SEBAGAI SUMBER KAIDAH NAHWU - Aang Saeful Milah (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2013)
Prophetic Hadits has been served as the secondary source for inducting Arabic grammar (Iim al-Nahwu) next to the Qur'an. It was Ibnu Malik the first grammarian who developed a concept of employing Hadith in postulating his theories. Even though it is not arguable that there had been grammarians who had done so prior to him, attentions that had been payed to Hadits by those grammarians seemed to be not in balance with Hadith which actually has been the most loquence language for the Arabs. There were three stands of grammarians upon the Hadits: Most grammarians refused Hadits and preferred ancient Arabic poetry more than Hadits, some others openly took it into account, and the rest took the middle position. This article aims at describing lbnu Maliks thoughts on the authority of Hadits as a source of Nahwu. He tried to prove that Hadits could, and still, play authoritative role in postulating theories of Nahwu. Key Words: Ibnu Malik, Nahwu, Hadith, Language